2017
DOI: 10.1111/rda.13023
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants protect proteins' anchorage to the bilayer by improving plasma membrane integrity of ram spermatozoa during liquid preservation in a soya lecithin‐based diluent

Abstract: Antioxidants are known to prevent the reactive oxygen species (ROS)-mediated peroxidative damage to the membrane lipids during hypothermic storage of mammalian spermatozoa. We hypothesized here that ROS also affect the lipid-protein interactions, thereby diminishing the membrane's integrity and proteins' anchorage to the bilayer. Antioxidants prevent these damages by scavenging the ROS. Ejaculates from Patanwadi rams were pooled after subjective evaluation and centrifuged using Percoll . Sperm pellet was resus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Similar results were also obtained in our study. We concluded that increase of plasma membrane integrity of sperm had a high correlation with antioxidant performance induced by SI (Paul and Smk 2017). The HOST was descried as a classical assay to evaluate function of sperm and integrity of physiological function of sperm plasma membrane (Lechniak et al 2003).…”
Section: Discussionmentioning
confidence: 97%
“…Similar results were also obtained in our study. We concluded that increase of plasma membrane integrity of sperm had a high correlation with antioxidant performance induced by SI (Paul and Smk 2017). The HOST was descried as a classical assay to evaluate function of sperm and integrity of physiological function of sperm plasma membrane (Lechniak et al 2003).…”
Section: Discussionmentioning
confidence: 97%
“…Seminal plasma contains sodium, potassium, protein, ascorbic acid, and many nutrients. Ascorbic acid, an antioxidant, keeps the plasma membrane from oxidative phosphorylation [23]. Meanwhile, sodium and potassium ions in seminal plasma play a key role in sperm metabolism through the plasma membrane [24].…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have shown the beneficial effects of catalase in semen cryopreservation. For instance, Paul et al (2017) found that the addition of catalase (100 IU/mL) and glutathione (10 mM), in soya lecithin-Tris-fructose extenders at 3-5°C for 48 h, improved various parameters of ram semen, such as motility and sperm velocity, improved the plasma membrane integrity, and reduced significantly the levels of MDA. Furthermore, Alomar et al (2016) demonstrated that adding catalase to ram semen extenders significantly reduced the formation of H 2 O 2 by live and dead sperm.…”
Section: Catalasementioning
confidence: 99%